Pulmonary complications and survival after autologous stem cell transplantation: predictive role of pulmonary function and pneumotoxic medications. Issue 3 (30th March 2017) - Scarlata, Simone; Annibali, Ombretta; Santangelo, Simona; Tomarchio, Valeria; Ferraro, Silvia; Armiento, Daniele; Scardocci, Alessandra; Arcese, William; Antonelli Incalzi, Raffaele; Avvisati, Giuseppe
Autologous stem cell transplantation (ASCT) is the standard of care for multiple myeloma patients eligible for high-dose therapy, lymphoma patients undergoing second-line treatments and for acute myelogenous leukaemia (AML) [1]. Immune system impairment and chemotherapies significantly increase the risk of infections, particularly pneumonia [2]. Overall, pulmonary complications, both infectious and non-infectious, occur in 40–60% of patients after stem cell transplantation [3], and are usually classiﬁed as early or late onset, depending on whether they occur within 100 days of the transplant [4]. The underlying disease and baseline pulmonary function, along with conditioning regimens consisting of carmustine, etoposide, aracytin and melphalan for lymphoma, melphalan alone for multiple myeloma or busulpan and cyclophosphamide for acute myeloid leukaemia, all concur to cause pulmonary complications [3, 4]. Pneumotoxic agents prior to ASCT associate with worse event/infection free survival and overall mortality http://ow.ly/1xkL308x3D2